Anti-cracking long-shelf-life plastic material for high-temperature shaft kiln and preparation method and application of anti-cracking long-shelf-life plastic material
By using long-shelf plastic materials for cracking resistance in high-temperature vertical kilns, the problem of refractory materials cracking in high-temperature environments is solved, the service life and insulation performance of the kiln are improved, and the effects of energy saving and cost reduction are achieved.
Patent Information
- Application Number
- CN202411818191.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-28
AI Technical Summary
The refractory materials of high-temperature vertical kilns are prone to cracking in high-temperature environments, resulting in shortening of the service life of the kiln and poor insulation performance, resulting in hot gas spillage, wasting energy and affecting the indicators of finished products inside the kiln.
A long-swelling plastic material for high-temperature vertical kilns is adopted. The material increases the number of closed micro-pores of the material through specific plasticizers, binding agents and treatment methods, improves thermal shock stability, and forms a micro-expanded state to offset the shrinkage of the material through the preparation method of magnesium-aluminum composite powder.
This material is not easy to crack in a high-temperature environment, which improves the service life of the kiln, reduces heat dissipation, saves energy, and reduces the cost of use. At the same time, there are more air closures inside, which reduces the demand for insulation layer and improves the insulation effect.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high-temperature shaft kilns, and in particular to a crack-resistant and long-shelf-life plastic material for a high-temperature shaft kiln, and a preparation method and application thereof. Background Art
[0002] At present, large-scale vertical kiln type industrial kilns have a high operating temperature, usually at 1700-1900℃, and are generally designed to have a long service life. If the working layer material is used improperly, it will greatly affect the service life of the kiln, and the cost of re-ignition or shutdown will be very huge. Therefore, it is necessary to design a refractory material with a long service life and a long shelf life to meet the special use requirements of high-temperature vertical kilns.
[0003] At present, the common problems of high temperature shaft kiln working lining are as follows:
[0004] (1) The kiln lining is generally designed to be thick, usually about 1 meter thick. During use, cracks often occur, causing the outer steel shell to turn red and be dangerous.
[0005] (2) The refractory materials commonly used in high-temperature vertical kiln linings are pure corundum or alumina-based castables. The integral casting method is used, which requires the production of large molds. At the same time, after construction, due to the thick masonry, cracks will occur during the curing or drying process.
[0006] (3) At present, high-temperature kiln linings are also built with high-purity corundum bricks, but the cost of the masonry is relatively high, and during use, the heat will also be lost along the brick joints.
[0007] (4) Another method is to use plastic to build the kiln, but plastic usually uses aluminum dihydrogen phosphate as a binder, or uses a clay system and adds water on site. The former has the problem of short plastic preservation time, which leads to dispersion during use, and the latter has the same problem of cracking as ordinary water-based castables because a large amount of water needs to be added during on-site mixing.
[0008] (5) Large vertical kilns on site all need to have a thicker insulation layer near the steel shell side. Most of the insulation layers are made of soft or hard aluminum silicate fiber materials, but they will recrystallize and gradually pulverize in a high-temperature environment, resulting in the loss of insulation effect during use.
[0009] During the alternating use of hot and cold conditions, the above-mentioned materials often have a large number of cracks due to their poor thermal shock stability. When the external insulation layer fails, a large amount of hot air will overflow, which will cause energy loss and damage the steel structure, resulting in poor structural stability.
[0010] In addition, due to the poor thermal insulation performance, the temperature inside the kiln fluctuates greatly, which wastes energy and affects the indicators of the finished products fired inside the vertical kiln. The indicators of the finished products fluctuate with the temperature fluctuations, and even become unqualified.
[0011] There is little research on refractory materials for high-temperature shaft kilns. For example, in the patent application "Kiln structure of an energy-saving shaft kiln (CN218210673U), it is mentioned that from the cold end to the hot end, there are an insulating layer, a heat-insulating layer and a working layer, and the working layer is a high-purity corundum castable material". The use of corundum castables for integral casting will produce cracks, and the high-purity corundum castables have poor thermal shock stability. The patent application "A lining material and production method for a lime shaft kiln (CN101597170A)" mentions the comprehensive masonry of unfired aluminum bricks and unfired phosphoric acid combined bricks for the lining. Summary of the invention
[0012] The present invention provides a crack-resistant, long-shelf-life plastic material for a high-temperature vertical kiln, and a preparation method and application thereof. The plastic material of the present invention adopts a special plasticizer, a binder and a treatment method, and after the fine powder is coated and the aggregate is soaked, it is ensured that the plastic material has a long plastic storage period. At the same time, after special treatment of the aggregate and the fine powder respectively, a large number of closed micropores will be formed inside the material during use, presenting a micro-expansion state, which greatly improves the thermal shock stability of the material, and there will be no cracking during use. It is very suitable for such high-temperature kiln applicable environment, improves service life, reduces heat dissipation, saves energy, and saves use costs.
[0013] [1] A crack-resistant and long-shelf-life plastic material for a high-temperature shaft kiln, wherein the raw materials include, by weight: 60-80 parts (e.g., 60 parts, 65 parts, 70 parts, 75 parts, etc.) of corundum component, 5-20 parts (e.g., 10 parts, etc.) of activated alumina powder, 10-30 parts (e.g., 15 parts, 20 parts, 25 parts, 30 parts, etc.) of magnesium-aluminum composite powder, 0.5-2 parts (e.g., 0.5 parts, 1 parts, 1.5 parts, 2 parts, etc.) of plasticizer, 6-12 parts (e.g., 6 parts, 8 parts, 9 parts, 10 parts, etc.) of binder, and 0.03-0.4 parts (e.g., 0.17 parts, 0.18 parts, 0.14 parts, etc.) of explosion-proof agent; the binder is aluminum sulfate solution I;
[0014] The corundum component includes modified corundum particles with a particle size greater than 0.045 mm and corundum fine powder with a particle size of 0-0.045 mm; the modified corundum particles are obtained by treating the corundum raw material with aluminum sulfate solution II; the treating with aluminum sulfate solution II specifically includes: immersing the corundum raw material in an excess of aluminum sulfate solution II at 50-80° C. for 1-2 days, so that the aluminum sulfate solution II is completely immersed in the open pores of the corundum raw material, taking out and drying to obtain the modified corundum particles;
[0015] The method for preparing the magnesium-aluminum composite powder comprises the following steps:
[0016] (1) mixing high-purity magnesia fine powder and high-purity activated alumina fine powder and ball-milling the mixture for 4-8 hours (e.g., 6 hours) to obtain a mechanically activated mixed powder;
[0017] (2) adding the mixed powder obtained in step (1) into a wheel mill, first adding polyisobutylene in the order of weight ratio of polyisobutylene to the mixed powder being 3-5:100 (e.g., 4:100, etc.), adding a plasticizer after rolling and stirring for a period of time, wherein the weight ratio of the plasticizer to the mixed powder is 0.25-1:100 (e.g., 0.5:100, etc.), rolling and stirring again to obtain the magnesium-aluminum composite powder; the plasticizer is one or both of dioctyl oxalate and dioctyl sebacate.
[0018] In some embodiments, the total weight of the corundum component, the activated alumina powder and the magnesium-aluminum composite powder in the high-temperature vertical kiln resistant and long-shelf life plastic material may be 100 parts.
[0019] In some embodiments, the density of the aluminum sulfate solution II for the high temperature shaft kiln anti-cracking and long shelf life plastic material may be 1.20-1.30 g / cm 3 .
[0020] In some embodiments, the crack-resistant and long-shelf-life plastic material for the high-temperature vertical kiln, the corundum raw material and the corundum fine powder may respectively contain 92wt%-97wt% of aluminum oxide and 3wt%-7wt% of magnesium oxide, and the physical phases may coexist as corundum phase and aluminum-magnesium spinel phase.
[0021] In some embodiments, the weight portion of the crack-resistant and long-shelf-life plastic material for high-temperature vertical kiln may be 5-15 parts, such as 10 parts.
[0022] In some embodiments, in the crack-resistant and long-shelf-life plastic material for high-temperature vertical kiln, the weight proportion of the modified corundum particles may be 50-75 parts, for example, 50 parts, 55 parts, 60 parts, 65 parts, etc.
[0023] In some embodiments, the high temperature vertical kiln uses a crack-resistant and long-shelf-life plastic material, and the particle size of the corundum raw material does not exceed 20 mm.
[0024] Further, in parts by weight, the particle size distribution of the corundum raw material may be:
[0025]
[0026] Furthermore, the corundum raw material can be treated by soaking aluminum sulfate solution II independently according to different particle size ranges. For example, in order to soak each particle size of corundum raw material separately, it is necessary to prepare a plurality of cylindrical pools with a diameter of 1m and a height of 1m in advance. The working layer of the pool is made of anti-corrosion material, with a discharge valve at the bottom, a dumping device and a pool wall heating device to facilitate discharge and internal solution heating. The density of the aluminum sulfate solution II used for soaking can be 1.20-1.30g / cm 3 During the soaking process, the temperature of aluminum sulfate solution II is maintained at 50-80°C. When the aggregate is placed in the pool for soaking, the aluminum sulfate solution II is used to completely submerge the modified corundum aggregate. The soaking time is 1-2 days, so that the aluminum sulfate solution II is completely immersed in the open pores of the corundum raw material. After taking it out, it is naturally dried for standby use.
[0027] The modified corundum particles after treatment in the present invention reduce the open porosity and retain the original closed pores, and at the same time, the Fe 2 O 3 Impurities such as plastics will react in advance during the soaking process, which not only reduces the plastic material confinement process, but also does not affect the shelf life of the plastic material.
[0028] The magnesium-aluminum composite powder of the present invention is firstly mixed with high-purity magnesium sand fine powder and high-purity active alumina fine powder by ball milling, and then mechanically activated. After mechanical activation, the crystal lattices of the two powders are distorted, and the two powders are fully mixed to reduce the temperature of magnesium-aluminum spinel formation, and the formation temperature of magnesium-aluminum spinel can be reduced to 800-100° C. During use, magnesium-aluminum spinel phase will be produced in situ, and a large number of micropores will be formed along with volume expansion, thereby improving the thermal shock resistance stability of the material.
[0029] In the preparation method of the magnesium-aluminum composite powder, after the treatment in step (2), a thin film will be coated around the magnesium-aluminum mixed powder, which can effectively avoid the problem of magnesium sand hydration during stirring when the binder aluminum sulfate solution I is added in the next step. At the same time, since the coated primary film is organic, it does not affect the reaction of magnesium-aluminum spinel under high temperature conditions.
[0030] In some embodiments, the crack-resistant and long-shelf-life plastic material for high-temperature vertical kiln, the particle size of the magnesium-aluminum composite powder may be 1-3 μm.
[0031] In some embodiments, in the method for preparing the crack-resistant and long-shelf-life plastic material for the high-temperature vertical kiln, the magnesium-aluminum composite powder, based on the total mass of the high-purity magnesia fine powder and the high-purity activated alumina as 100%, the mass proportion of the high-purity magnesia fine powder may be 10%-34% (for example, 22%, etc.), and the mass proportion of the high-purity activated alumina fine powder may be 66%-90% (for example, 78%, etc.).
[0032] In some embodiments, in the crack-resistant and long-shelf-life plastic material for high-temperature vertical kiln, in the method for preparing the magnesium-aluminum composite powder, the high-purity magnesia fine powder has a MgO content of ≥99.0wt%, and a median diameter D50 of 3-6μm.
[0033] In some embodiments, the high-temperature vertical kiln anti-cracking long-shelf-life plastic material, the method for preparing the magnesium-aluminum composite powder, the high-purity activated alumina fine powder Al 2 O 3 The content is ≥99.7wt%, and the median diameter D50 can be 2-4μm.
[0034] In some embodiments, in the method for preparing the crack-resistant and long-shelf-life plastic material for a high-temperature vertical kiln, the number average molecular weight of the polyisobutylene can be controlled within 200-10000 g / mol, and can be further controlled within 7000-9000 g / mol.
[0035] In some embodiments, in the method for preparing the crack-resistant and long-shelf-life plastic material for high-temperature vertical kiln, the time for rolling and stirring after adding polyisobutylene can be 10-30 minutes, for example, 20 minutes.
[0036] In some embodiments, in the method for preparing the crack-resistant and long-shelf-life plastic material for high-temperature vertical kiln and the magnesium-aluminum composite powder, the time for rolling and stirring again after adding the plasticizer can be 10-30 minutes, for example, 20 minutes.
[0037] In some embodiments, the high temperature shaft kiln anti-cracking long shelf life plastic material, the activated alumina powder Al 2 O 3 Content ≥99.7wt%, specific surface area can be 2.0-3.0m 2 / g, and the median diameter D50 may be 0.5-2.0 μm. For example, the activated alumina powder may be selected from 07RAL, 15RAL, etc., which have good sintering performance.
[0038] In some embodiments, the crack-resistant and long-shelf-life plastic material for high-temperature vertical kiln, the plasticizer may include one or more of dioctyl oxalate, dioctyl sebacate, trioctyl phosphate, and triphenyl phosphate.
[0039] In some embodiments, the crack-resistant and long-shelf-life plastic material for high-temperature vertical kiln, based on the sum of the weight parts of the corundum component, the activated alumina powder and the magnesium-aluminum composite powder as 100%, the weight percentage of the plasticizer can be 0.5%-2%, for example 0.5%, 1%, 1.5%, 2%, etc.
[0040] In some embodiments, the density of the aluminum sulfate solution I of the high temperature shaft kiln anti-cracking long-shelf life plastic material may be 1.20-1.30 g / cm 3 .
[0041] In some embodiments, the anti-cracking and long-shelf-life plastic material for high-temperature shaft kiln, the explosion-proof agent may include one or more of metal aluminum powder and polypropylene fiber. Further, the diameter of the polypropylene fiber may be 10-20 μm, the length may be 4-6 mm, and the melting point temperature may be 100-120°C. The polypropylene fiber with the above characteristics has the characteristics of high dispersibility, ultra-fine diameter and low-temperature melting, which can form a gas channel and effectively prevent the cracking of the masonry during baking.
[0042] In some embodiments, the anti-cracking and long-shelf-life plastic material for high-temperature shaft kiln, the explosion-proof agent may include metal aluminum powder and polypropylene fiber. Further, the weight portion of the metal aluminum powder may be 0.02-0.04 parts; the weight portion of the polypropylene fiber may be 0.1-0.15 parts.
[0043] [2] The method for preparing the crack-resistant and long-shelf-life plastic material for high-temperature vertical kiln according to [1] comprises the steps of:
[0044] S1, adding corundum component, activated alumina powder, magnesium-aluminum composite powder, plasticizer, binder and explosion-proof agent into a wheel mill and fully rolling and stirring;
[0045] S2, the material obtained in step S1 is extruded and shaped by a mud extruder to obtain the crack-resistant and long-shelf-life plastic material for the high-temperature vertical kiln.
[0046] In some embodiments, the material temperature can be controlled at 50-70° C. during the rolling and mixing process in step S1.
[0047] In step S1, the wheel roller can be equipped with a chassis heating system for controlling the temperature of the material during the rolling and mixing process.
[0048] The anti-cracking and long-shelf-life plastic material for high-temperature vertical kiln of the present invention can be stored for up to 2 years and still has good plasticity, which greatly improves the cheapness of storage and transportation and saves the procurement cost of the enterprise.
[0049] [3] Application of the anti-cracking and long-shelf-life plastic material for high-temperature vertical kilns according to [1] in the construction of high-temperature vertical kilns. In the application, the high-temperature vertical kiln can achieve a better insulation effect without the need for an insulation layer or by reducing the number of insulation layers.
[0050] Compared with the prior art, the present invention has the following beneficial effects:
[0051] 1) Using modified corundum particles soaked in aluminum sulfate as aggregate not only reduces the open porosity of the aggregate, but also perfectly retains the closed pores of the corundum raw material particles, increases the amount of overall closed micropores in the plastic material, and improves the thermal shock stability of the material. In addition, during the soaking process, the amount of reactants, such as Fe 2 O 3 , it is possible to achieve the effect of increasing the shelf life of plastic materials without trapping the materials.
[0052] 2) The magnesium-aluminum composite powder is wrapped with polyisobutylene to form a thin film, which can effectively prevent the hydration problem of magnesia sand during the later mixing and storage process.
[0053] 3) When using the mechanically activated magnesium-aluminum composite powder, the magnesium-aluminum spinel phase can be formed in situ at a relatively low temperature. During the reaction, expansion will occur, which will offset the shrinkage of the plastic material, present a micro-expansion state, and leave more closed micropores, which is beneficial to improve the thermal shock stability and crack resistance of the plastic material.
[0054] 4) The kiln built with the plastic material designed by the present invention has a large number of closed air holes inside, so it is not necessary to design a thermal insulation layer or reduce the number of thermal insulation layers to achieve a better thermal insulation effect. DETAILED DESCRIPTION
[0055] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only intended to illustrate the present invention and are not intended to limit the scope of the present invention. The operating methods in the following examples where no specific conditions are indicated are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0056] The raw material composition and dosage (unit: weight parts) of the high temperature vertical kiln resistant cracking and long shelf life plastic material of Examples 1-5 are shown in Table 1.
[0057] Table 1
[0058]
[0059] The raw material composition and dosage (unit: weight part) of the plastic materials of Comparative Examples 1-4 are shown in Table 2.
[0060] Table 2
[0061]
[0062] In Table 1 and Table 2:
[0063] The corundum raw material contains 92wt%-97wt% of aluminum oxide and 3wt%-7wt% of magnesium oxide, and the physical phases are coexistent of corundum phase and aluminum-magnesium spinel phase.
[0064] The modified corundum particles are obtained by immersing corundum raw materials of corresponding particle size range in aluminum sulfate solution II; the aluminum sulfate solution II treatment specifically comprises: immersing the corundum raw materials in excess of a density of 1.20-1.30 g / cm 3 The modified corundum particles are immersed in an aluminum sulfate solution II at 50-80°C for 1 day to allow the aluminum sulfate solution II to completely penetrate into the open pores of the corundum raw material, and then taken out and dried to obtain modified corundum particles.
[0065] The corundum fine powder contains 92wt%-97wt% of aluminum oxide and 3wt%-7wt% of magnesium oxide, and the physical phases are coexistent of corundum phase and aluminum-magnesium spinel phase.
[0066] The preparation method of magnesium-aluminum composite powder comprises the following steps:
[0067] (1) mixing high-purity magnesia fine powder and high-purity activated alumina fine powder with ball milling for 6 hours to obtain a mechanically activated mixed powder; taking the total mass of the high-purity magnesia fine powder and the high-purity activated alumina as 100%, the mass proportion of the high-purity magnesia fine powder is 22%, and the mass proportion of the high-purity activated alumina fine powder is 78%; the MgO content of the high-purity magnesia fine powder is ≥99.0wt%, and the median diameter D50 is 3-6μm; the high-purity activated alumina fine powder Al 2 O 3 Content ≥ 99.7wt%, median diameter D50 is 2-4μm;
[0068] (2) adding the mixed powder obtained in step (1) into a wheel mill, first adding polyisobutylene with a number average molecular weight of 7000-9000 g / mol, wherein the weight ratio of polyisobutylene to the mixed powder is 4:100, and then rolling and stirring for 20 minutes, adding a plasticizer, wherein the weight ratio of the plasticizer to the mixed powder is 0.5:100, and rolling and stirring for another 20 minutes to obtain the magnesium-aluminum composite powder; the plasticizer is dioctyl oxalate.
[0069] In the above-mentioned method for preparing magnesium-aluminum composite powder, the mixed powder obtained according to step (1) is the uncoated magnesium-aluminum composite powder.
[0070] Activated Alumina Powder Al 2 O 3 Content ≥99.7wt%, specific surface area 2.0-3.0m 2 / g, and the median diameter D50 is 0.5-2.0μm.
[0071] The diameter of polypropylene fiber is 10-20μm, the length is 4-6mm, and the melting point temperature is 100-120℃.
[0072] The density of the binder is 1.20-1.30g / cm 3 Aluminum sulfate solution I.
[0073] The preparation method of the plastic material of each embodiment and comparative example comprises the steps of:
[0074] S1, adding the raw materials shown in the embodiments and comparative examples in Table 1 and Table 2 to a wheel mill and fully rolling and stirring; the material temperature is controlled at 50-70°C during the rolling and stirring process;
[0075] S2, the material obtained in step S1 is extruded and shaped by a mud extruder to obtain a plastic material.
[0076] The test results of the plastic material properties of each embodiment and comparative example are shown in Table 3.
[0077] Table 3
[0078]
[0079] In addition, it should be understood that after reading the above description of the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.
Claims
1. A crack-resistant and long-shelf-life plastic material for high-temperature shaft kiln, characterized in that: The raw material composition includes, by weight: 60-80 parts of corundum component, 5-20 parts of activated alumina powder, 10-30 parts of magnesium-aluminum composite powder, 0.5-2 parts of plasticizer, 6-12 parts of binder, and 0.03-0.4 parts of explosion-proof agent; the binder is aluminum sulfate solution I; The corundum component includes modified corundum particles with a particle size greater than 0.045 mm and corundum fine powder with a particle size of 0-0.045 mm; the modified corundum particles are obtained by treating the corundum raw material with aluminum sulfate solution II; the treating with aluminum sulfate solution II specifically includes: immersing the corundum raw material in an excess of aluminum sulfate solution II at 50-80° C. for 1-2 days, so that the aluminum sulfate solution II is completely immersed in the open pores of the corundum raw material, taking out and drying to obtain the modified corundum particles; The preparation method of the magnesium-aluminum composite powder comprises the steps of: (1) mixing high-purity magnesia fine powder and high-purity activated alumina fine powder and ball-milling the mixture for 4-8 hours to obtain a mechanically activated mixed powder; (2) adding the mixed powder obtained in step (1) into a wheel mill, first adding polyisobutylene in the order of 3-5:100 by weight of the polyisobutylene to the mixed powder, and adding a plasticizer after rolling and stirring for a period of time, wherein the weight ratio of the plasticizer to the mixed powder is 0.25-1:100, and rolling and stirring again to obtain the magnesium-aluminum composite powder; the plasticizer is one or both of dioctyl oxalate and dioctyl sebacate.
2. The anti-cracking and long-shelf-life plastic material for high-temperature shaft kiln according to claim 1, characterized in that: The total weight of the corundum component, the activated alumina powder and the magnesium-aluminum composite powder is 100 parts.
3. The anti-cracking and long-shelf-life plastic material for high-temperature shaft kiln according to claim 1, characterized in that: The density of the aluminum sulfate solution II is 1.20-1.30 g / cm 3 ; The corundum raw material and the corundum fine powder contain 92wt%-97wt% of aluminum oxide and 3wt%-7wt% of magnesium oxide respectively, and the physical phases are both coexistent of corundum phase and aluminum-magnesium spinel phase; The particle size of the corundum raw material does not exceed 20 mm; The weight portion of the modified corundum particles is 50-75 parts; The weight portion of the corundum fine powder is 5-15 parts.
4. The anti-cracking and long-shelf-life plastic material for high-temperature shaft kiln according to claim 1 or 3, characterized in that: In parts by weight, the particle size distribution of the corundum raw material is: The corundum raw materials are treated with aluminum sulfate solution II independently according to different particle size ranges.
5. The anti-cracking and long-shelf-life plastic material for high-temperature shaft kiln according to claim 1, characterized in that: The particle size of the magnesium-aluminum composite powder is 1-3 μm; Taking the total mass of the high-purity magnesia fine powder and the high-purity activated alumina as 100%, the mass of the high-purity magnesia fine powder accounts for 10%-34%, and the mass of the high-purity activated alumina fine powder accounts for 66%-90%; The high-purity magnesia fine powder has a MgO content of ≥99.0wt% and a median diameter D50 of 3-6μm; The high-purity activated alumina fine powder has an Al2O3 content of ≥99.7wt% and a median diameter D50 of 2-4μm; The number average molecular weight of the polyisobutylene is controlled within the range of 200-10000 g / mol, and further controlled within the range of 7000-9000 g / mol; The rolling and stirring time after adding polyisobutylene is 10-30 minutes; After adding the plasticizer, the time for rolling and stirring again is 10-30 minutes.
6. The anti-cracking and long-shelf-life plastic material for high-temperature shaft kiln according to claim 1, characterized in that: The activated alumina powder has an Al2O3 content of ≥99.7wt% and a specific surface area of 2.0-3.0m 2 / g, median diameter D50 is 0.5-2.0μm; The plasticizer includes one or more of dioctyl oxalate, dioctyl sebacate, trioctyl phosphate, and triphenyl phosphate; The weight percentage of the plasticizer is 0.5%-2% based on the sum of the weight of the corundum component, the activated alumina powder and the magnesium-aluminum composite powder as 100%; The density of the aluminum sulfate solution I is 1.20-1.30 g / cm 3 ; The explosion-proof agent includes one or more of metal aluminum powder and polypropylene fiber; The polypropylene fiber has a diameter of 10-20 μm, a length of 4-6 mm, and a melting point of 100-120° C.
7. The anti-cracking and long-shelf-life plastic material for high-temperature shaft kiln according to claim 1 or 6, characterized in that: The explosion-proof agent includes metal aluminum powder and polypropylene fiber; The weight portion of the metal aluminum powder is 0.02-0.04 parts; The weight portion of the polypropylene fiber is 0.1-0.15 parts.
8. The method for preparing the crack-resistant and long-shelf-life plastic material for high-temperature shaft kiln according to any one of claims 1 to 7, characterized in that: Includes steps: S1, adding corundum component, activated alumina powder, magnesium-aluminum composite powder, plasticizer, binder and explosion-proof agent into a wheel mill and fully rolling and stirring; S2, the material obtained in step S1 is extruded and shaped by a mud extruder to obtain the crack-resistant and long-shelf-life plastic material for the high-temperature vertical kiln.
9. The preparation method according to claim 8, characterized in that: During the rolling and stirring process in step S1, the material temperature is controlled at 50-70°C.
10. Use of the anti-cracking and long-shelf-life plastic material for high-temperature vertical kiln according to any one of claims 1 to 7 in building a high-temperature vertical kiln.
Citation Information
Patent Citations
Inner lining material for lime shaft kiln and production method thereof
CN101597170A
Kiln body structure of energy-saving shaft kiln
CN218210673U